Effects of potassium application on yield attributes, yield and grain quality of lentil in terrace soil of Joydebpur (Bangladesh Journal of Agricultural Research, 2020)
An experiment was conducted in the research field of Pulses Research Sub-Station, BARI, Gazipur during two consecutive years of 2015-16 and 2016-17 to determine the suitable dose of potassium for achieving higher yield attributes, nodulation, nutrient concentration and yield maximization of lentil. There were 5 treatments viz. T1 = Control, T2 = 30 kg K ha-1, T3= 40 kg K ha-1, T4= 50 kg K ha-1 and T5= 60 kg K ha-1 along with the blanket dose of fertilizers of N, P, S, Zn and B @ 15, 20, 10, 2 and 1.5 kg ha-1, respectively for all treatments. The experiment was laid out in randomized complete block design (RCBD) with three replications. Results revealed that the highest seed yield (1092 kg ha-1) of lentil (mean of two years) was found in T4 followed by T5 treatment and the lowest (736 kg ha-1) was noted in K control (T1) treatment. The highest % yield increase over control (48.3%) was recorded from T4 treatment. The maximum nodulation was found in T5 followed by T4 treatment. The highest protein (26.9%), N, P, K, S, Zn and B concentrations of lentil seed were recorded in T4 treatment. Therefore, the results suggest that the appliction of 50 kg K ha-1 along with N15P20S10Zn2B1.5 kg ha-1 are optimum for achieving higher yield potential of lentil in terrace soils of Bangladesh.Bangladesh J. Agril. Res. 44(4): 599-607, December 2019